Korelasi antara Motivasi dan Karakteristik Suasana pada Ruang Terbuka Publik di Kota Palembang - Karina Karina (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2025)
Public open space can provide a special identity for a city. Generally, the shape of public open spaces must be able to accommodate a variety of user activities and have characteristics that attract people to come. The purpose of this study is to determine the correlation between motivation and atmosphere characteristics in public open spaces in Palembang City. This research uses quantitative methods that are explanatory. The data collected by using the semantic-differential (SD-method) with the sample selection using snowball-non-random-sampling. The results of the latent variable analysis and Multivariate Correlation Analysis are in the form of a relationship between motivation and the atmosphere in public open spaces in Palembang City. The results of this study indicate that the motivation of the people who come to open public spaces has reasons, that are refreshment, achievement and interaction. This motivation is supported by the influence of the atmosphere in public open space which is assessed from two aspects, such as orderliness and natural environment.